2020
DOI: 10.3390/rs12040736
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Spatial Resolution and Retrieval Frequency on Applicability of Satellite-Predicted PM2.5 in Northern China

Abstract: Satellite aerosol optical depth (AOD) products have been widely used in estimating fine particulate matter (PM2.5) concentrations near the surface at a regional scale, and perform well compared with ground measurements. However, the influence of limitations such as retrieval frequency and the spatial resolution of satellite AODs on the applicability of predicted PM2.5 values has been rarely considered. With three widely used MODIS AOD products, including Multi-Angle Implementation of Atmospheric Correction (MA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…The performance of the AOD-based PM 2.5 retrieval models may be affected by the AOD spatial resolution. However, the conclusions of this issue are not consistent in previous studies [17,[21][22][23]; their work mainly focuses on the traditional statistical regression models, and such analysis is lacking for machine learning models. Lee et al [23] used the linear mixed-effect model to estimate PM 2.5 in the Southeastern United States.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…The performance of the AOD-based PM 2.5 retrieval models may be affected by the AOD spatial resolution. However, the conclusions of this issue are not consistent in previous studies [17,[21][22][23]; their work mainly focuses on the traditional statistical regression models, and such analysis is lacking for machine learning models. Lee et al [23] used the linear mixed-effect model to estimate PM 2.5 in the Southeastern United States.…”
Section: Introductionmentioning
confidence: 69%
“…They found that the model using 1 km AOD data showed a better performance than that using 10 km AOD data. Li et al [21] conducted similar work in northern China but found that the 1 km model performance was slightly lower than the 10 km model. The YRD region also experienced such a difference in performance between 3 and 10 km AOD data [17].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Yang et al [32] studied the relationship between PM 2.5 and AOD using AOD data obtained from MODIS, and found that the meteorological influence on PM and AOD was strong in June. Li et al [33] estimated daily PM 2.5 concentrations in the Beijing-Tianjin-Hebei region of northern China during 2017 using a mixed-effects model. The impact of the spatial resolution and sampling frequency of the AOD on PM 2.5 prediction was then assessed.…”
Section: Introductionmentioning
confidence: 99%
“…Satellite-derived AOD is the overall extinction value of the atmospheric column, and satellite aerosol products have the advantage of global coverage. Studies have shown that AOD has a good correlation with PM 2.5 concentrations near the surface [3], and it has been widely used in the estimation of PM 2.5 concentrations [4]. The PM 2.5 concentrations can be estimated by establishing a linear or nonlinear relationship between AOD and PM 2.5 .…”
Section: Introductionmentioning
confidence: 99%